T1 Signal Intensity and Height of the Anterior Pituitary in Neonates: Correlation with Postnatal Time - Kitamura, E.; Miki, Y.; Kawai, M.; Itoh, H.; Yura, S.; Mori, N.; Sugimura, K.; Togashi, K. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The anterior pituitary of a term neonate is usually hyperintense on T1-weighted MR images, which may represent histologic changes of the gland due to the effect of high estrogen levels during the fetal period; however, MR findings of a preterm neonate have not been fully evaluated. The purpose of this study was to investigate whether intensity and size of the neonatal anterior pituitary on MR images obtained near term of corrected age correlates with the gestational age at birth or postnatal time.MATERIALS AND METHODS: Data of 88 consecutive neonates (gestational age, 24–41 weeks; mean, 31.5 weeks) were analyzed. All of the neonates underwent MR imaging at a corrected age of 0 months ± 4 weeks. Relative signal intensity of the anterior pituitary compared with that of the pons on T1-weighted sagittal images was calculated. Height of the pituitary was also measured. Stepwise regression analysis was performed to evaluate the effects of gestational age at birth and postnatal time on the relative signal intensity and on the pituitary height.RESULTS: The relative signal intensity significantly negatively correlated with postnatal time (P = .001) but not with gestational age at birth (P = .42). Pituitary height significantly negatively correlated with postnatal time (P = .049) but not with gestational age at birth (P = .071).CONCLUSION: A significant negative correlation exists between postnatal time and signal intensity on T1-weighted MR images of the anterior pituitary obtained near term. A nonhyperintense anterior pituitary is a normal MR finding of preterm neonates when imaged near term.